BiFeO3 induced enhancement in multiferroic properties of PbFe0.5Nb0.5O3. Issue 16 (November 2018) - Dadami, Sunanda T.; Shivaraja, I.; Deshpande, S.K.; Rayaprol, Sudhindra; Angadi, Basavaraj
Abstract: Magnetic susceptibility, Electron Paramagnetic Resonance (EPR), dielectric and ferroelectric studies of (1-x) PbFe0.5 Nb0.5 O3 (PFN) - (x)BiFeO3 (BFO) (PFN - BFO) with x = 0.1, 0.2, 0.3 and 0.4 solid solutions have been systematically investigated in order to study the enhanced multiferroic properties. Susceptibility measurements show the enhanced magnetic ordering ( T N1 ) of PFN from 155 K to 260 K and to 310 K for x = 0.1 and 0.2, respectively, however, for x = 0.3 and x = 0.4 it is shifted to above room temperature. M-H loops measured at 5 K for x = 0.1, 0.2 and 0.3 exhibits a small opening in the loop, whereas for x = 0.4, a clear S shaped loop is observed which is a characteristic feature of weak ferromagnetic materials. At room temperature, samples with x = 0.2, 0.3 and 0.4 exhibits antiferromagnetic ordering whereas x = 0.1 exhibits paramagnetic behaviour. EPR spectra measured at three selected temperatures (200 K, 300 K and 450 K) exhibits single Lorentzian line in all solid solutions which is attributed to Fe in + 3 state. The EPR spectra become broaden at and above room temperature in all solid solutions, corresponding to the antiferromagnetic nature, which is confirmed by the magnetic measurements. Temperature dependent dielectric studies exhibit a clear anomaly around the Néel temperature ( T N1 ) at 240 K, 260 K, 310 K and 318 K for x = 0.1, 0.2, 0.3 and 0.4 respectively, clearly signalling the existence of magnetoelectric coupling in these compounds. The ferroelectric ( P vs. E ) loops confirm the existence of ferroelectric ordering. On the basis of the above studies, it is confirmed that PFN-BFO solid solutions are the potential candidates for multifunctional applications.